Maternal Healthcare Services and the Health Workers among the Migrant Slum Dwellers of Bangalore City, Karnataka, India - Suchismita Mishra; T. Rajendra Prasad (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2019)
The health workers play a variety of roles which include provision of outreach, information, referral, advocacy and other support to promote health and help people meet their healthcare. The poor migrants usually settle in unauthorized slums or settlements. The migrant health is found in a disadvantageous position due to poor access to healthcare services. The present paper examines the maternal healthcare services provided by the peripheral health workers among the interstate migrants living in slums of Bangalore city. After conducting a pilot survey, five slums (migrant camps/non-notified slums) were identified based on the criteria of 1) inter- state migration 2) year of migration <7 years 3) having more than 100 households. Mothers with a child below 2 years (n=100) were interviewed with a pretested questionnaire. Qualitative data were collected from the mothers, key informants and healthcare workers through in- depth interviews. The maternal healthcare services by the health workers are not able to reach the migrant population due to migrants’ location of staying and many women went back to their native place for child delivery. The migrants who moved for delivery to their native place (32.4%) accessed the services of the health workers better than the respondents who stayed in the Bangalore city (13.5%). Similar situation was found for the visit of the heath workers for post-natal care. Some institutional lacuna like lack of space, toilets, water and also the shortage of staff etc. were pointed out by the health workers, which are required. The study warrants the need to understand the realities and healthcare needs of the migrant population. A better mechanism should be developed to improve the services of peripheral health workers in delivering primary healthcare services like maternal health care.